From mousedeer to mouse : Malaysian animation at the crossroads / Hassan Abdul Muthalib - Abdul Muthalib, Hassan (UPENA, 2006)
Since long-form animation began commercially in 1995, there has been an unprecedented production of animation for television and cinema. However, Malaysian animation is at the crossroads. Even though foreign sales have been made, it is not cost-effective for producers to continue making animation. The problem is further compounded with the large number of graduates entering the industry. What needs to be done so that Malaysia will not lose out in the production of animation films and TV series featuring local stories and characters that can effectively reach out to young people, and at the same time, be able to appeal to a global audience?